Potret Pemerintahan Mesir Dalam Antologi “Kȃnat Lanȃ Authȃn” Karya Faruq Juwaidah (Analisis Sosiologi Sastra) - Sammad Hasibuan (Institut Agama Islam Negeri Metro, 2021)
This study aims to determine the description of Egyptian goverment and the attitude of the poet as Egyptian citizens in the anthology Kȃnat Lanȃ Authȃn by Faruq Juwaidah. Poetry as a type of literary work, apart from using beautiful and dense language in its structure, is also able to represent the social conditions of society at a certain time. The method chosen by researcher in this research is descriptive-qualitative method. Meanwhile, the approach used to analyze poetry is the sociological approach of literature, especially literature as a representation of society. Based on the results of the discussion, the authors in this study found a picture of Egyptian goverment contained in the anthologyKȃnat Lanȃ Authȃnby Faruq Juwaidah, as (1) Egyptian Government is described as an authoritariangovernment, (2) unfair to the Egyptian people (3) more in favor to the West, (4) Faruq as the Egyptian people criticizes this behavior, and (5) invite the government and the people to love and oriented to Egypt even though in a a simple life.